Violence and social orders a conceptual framework for interpreting recorded human history - North, Douglass Cecil 1920-2015 (Cambridge Univ. Press, 2009)
All societies must deal with the possibility of violence, and they do so in different ways. This study integrates the problem of violence into a larger social science and historical framework, showing how economic and political behavior are closely linked ...